Regulation of quorum sensing activities by the stringent response gene rsh in sphingomonads is species-specific and culture condition dependent - Xiao, Yue; Chen, Xin; Lu, Hang; Jiang, Tingting; Wang, Yichun; Liang, Luyi; Dobretsov, Sergey; Huang, Yili (Frontiers in Microbiology, 2024)
Stringent response and quorum sensing (QS) are two essential mechanisms that control bacterial global metabolism for better survival. Sphingomonads are a clade of bacteria that survive successfully in diverse ecosystems. In silico survey indicated that 36 out of 79 investigated sphingomonads strains contained more than one luxI homolog, the gene responsible for the biosynthesis of QS signal acyl homoserine lactones (AHLs).Investigation of the regulatory effects of the stringent response gene rsh on QS related bioactivities were carried out using rsh mutants of Sphingobium japonicum UT26 and Sphingobium sp. SYK-6, both had three luxI homologs. Results indicated that deletion of rsh upregulated the overall production of AHLs and extracellular polymeric substances (EPS) in both UT26 and SYK-6 in rich medium, but affected expressions of these luxI/luxR homologs in different ways. In the poor medium (1% LB), rsh mutant of SYK-6 significantly lost AHLs production in broth cultivation but not in biofilm cultivation. The regulatory effects of rsh on QS activities were growth phase dependent in UT26 and culture condition dependent in SYK-6. Our results demonstrated the negative regulatory effect of rsh on QS activities in sphingomonads, which were very different from the positive effect found in sphingomonads containing only one luxI/R circuit. This study extends the current knowledge on the intricate networks between stringent response and QS system in sphingomonads, which would help to understand their survival advantage.